Drug-responsive versus drug-refractory mesial temporal lobe epilepsy: a single-center prospective outcome study. Issue 7 (3rd October 2019) - Stefanatou, Maria; Gatzonis, Stylianos; Peskostas, Antonis; Paraskevas, George; Koutroumanidis, Michael
ABSTRACT: Objectives : To evaluate clinical, electrophysiological, and neuroradiological factors which correlate with the prognosis in patients with mesial temporal lobe epilepsy (MTLE). Methods : This was a single-center prospective outcome study in patients with MTLE. The patients' family history, clinical characteristics, neurophysiological data (electroencephalography – EEG), neuroimaging, antiepileptic therapy, and outcome were collected and analyzed. The population was divided into four groups depending on the frequency of the seizures when they attended their last follow up. All variables and outcome measures were compared between the four groups. Results : In total 83 consecutive patients were included within the four groups. Group 1 (seizure-free) consisted of 7 patients, (9%), Group 2 (rare seizures) consisted of 15 patients (18%), Group 3 (often seizures) consisted of 30 patients (36%), and Group 4 (very often seizures) consisted of 31 patients (37%). The groups did not differ significantly in demographic characteristics. There was a strong positive correlation between resistance to therapy and sleep activation on EEG (p = 0.005), occurrence of focal to bilateral seizures (p = 0.007), automatisms (p = 0.004), and the number of previously used antiepileptic drugs (AEDs) (p = 0.002). There was no association between febrile convulsions (FC), hippocampal sclerosis (HS), and the outcome that was found. Conclusion : MTLE is a heterogeneous syndrome. Establishing the factors responsible for, and associated with, drug resistance is important for optimal management and treatment, as early identification of drug resistance should then ensure a timely referral for surgical treatment is made. This prospective study shows that sleep activation on EEG, ictal automatisms, occurrence of focal to bilateral tonic-clonic seizures, and increased number of tried AEDs are negative prognostic factors.